University-Industry Relations in the Oil and Gas Sector in Russia - Cilento, Marco; Tinti, Alessandro (PARTECIPAZIONE E CONFLITTO, 2023)
Russian technical universities carry on the tradition of Soviet-era industrial institutes by providing skilled labour force to the industry. In recent years university-industry collaboration has grown in size and depth to include several other functions. This study explores university-industry relations in the oil and gas sector. Taking cues from the Triple Helix theory, a comparison is made between two renowned technical universities in Western Siberia that have been adopting different models of cooperation with industrial partners. The analysis shows that university's mission, funding strategies, and organizational culture determine the pace of cooperation. Findings underline the high regional engagement of both academic institutions, which figure as crucial nodes of the oil and gas value chain. On the background of increasing state pressure on higher education institutions to become more entrepreneurial, it is argued that technical universities are set to become crucial innovation actors in the coming years. This enables a more nuanced look at oil and gas governance in today's Russia and offers new insight into the role played by refashioned elite universities.